Implementation of Character Education in Implementing Students' Social Attitudes Through Subject Subjects Social Sciences at Mulia IT Elementary School - Azzahra, Siti Fatihah; Taqwani, Azhara Nurul (Berpusi Publishing, 2024)
This research aims to describe the implementation of character education in instilling students' social attitudes through social studies subjects at SD IT Mulia. The research method used is a descriptive qualitative approach, the data source is the result of interviews conducted by the author with the principal, class teachers and students at SD IT Mulia after conducting observations in the school environment. The data results are then analyzed and matched with supporting literature studies to be described in words. Based on the research results, it is known that the implementation of character education at SD IT Mulia has been carried out well. Application is not only carried out in learning within the school environment but also within the community. In its implementation, the role and cooperation between teachers and parents of students is important so that the efforts that have been made are realized.